2013
DOI: 10.1155/2013/961926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Chinese Herbal Formula (Invigorating Kidney and Strengthening Spleen) in Chronic Hepatitis B Virus Carrier: Results from a Multicenter, Randomized, Double-Blind, and Placebo-Controlled Trial

Abstract: A Chinese Herbal Formula (CHF) has acquired a certain therapeutic effect on chronic HBV infection. To assess the efficacy and safety of CHF on HBV replication in chronic HBV carriers, we performed a randomized, double-blind, and placebo-controlled trial involving patients from 16 centers. A total of 300 confirmed chronic HBV carriers were randomized at baseline in a ratio of 2 : 1 to receive either CHF or placebo for 52 weeks. The results showed that a greater proportion of CHF than placebo treated patients ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…A recent study showed that after treatment with interferon, 17.54% of patients with normal ALT but significant liver inflammation or fibrosis (G4, S3) demonstrated a sustained virologic response, which is significantly lower than those patients with elevated ALT (28.57%)[ 38 ]. Our study modified the TCM compound therapy from our previous national science and technology major project during the 11th five-year plan period[ 20 ] and extended the treatment course to 96 wk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that after treatment with interferon, 17.54% of patients with normal ALT but significant liver inflammation or fibrosis (G4, S3) demonstrated a sustained virologic response, which is significantly lower than those patients with elevated ALT (28.57%)[ 38 ]. Our study modified the TCM compound therapy from our previous national science and technology major project during the 11th five-year plan period[ 20 ] and extended the treatment course to 96 wk.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the HBeAg clearance and virologic response of the treated group were significantly better than that of the control group[ 19 ]. Preliminary clinical multicenter research of short courses of treatment during the national 11th five-year period project indicated that the decrease of HBV DNA was greater than 2 log by 17.5%, and the decrease of hepatitis B surface antigen (HBsAg) by 1 log was about 10% after 52 wk of ICE intervention[ 20 - 22 ]. In addition, liver histological results showed significant improvements in liver fibrosis, and immunohistochemistry showed significant decreases in the expression of HBsAg and hepatitis B core antigen (HBcAg) in responding patients.…”
Section: Introductionmentioning
confidence: 99%
“…After 52 weeks of treatment, the treatment group had a more marked decrease in the mean concentration of serum HBsAg than the control group did. The treatment group had a significant increase in IFN-γ, suggesting that FZJDT was able to modulate host immune function (24).…”
Section: Extracts In and Formulations Of Tcms To Treat Hbvmentioning
confidence: 95%
“…Over 90 % of chronic hepatitis B patients received the TCM therapy [ 24 ]. Preclinical and clinical trials, which were performed in China, indicated that some traditional Chinese medicine preparations, like phyllanthus urinaria, decoction of small bupleurum (a medicinal root found natively in East Asia), matrine (an alkaloid found in plants from the Sophora genus with anticancer activity), or rhubarb, had a potential effect on inhibiting HBV replication, regulating the hosts’ immune function, and improving liver function [ 25 , 26 ]. A short-term clinical follow-up study found that matrine treatment could result in a similar curative effect as interferon in HBeAg seroconversion and HBV DNA reduction [ 27 ].…”
Section: Drugs Available For Antiviral Therapy In Chinamentioning
confidence: 99%
“…A short-term clinical follow-up study found that matrine treatment could result in a similar curative effect as interferon in HBeAg seroconversion and HBV DNA reduction [ 27 ]. The small bupleurum decoction and phyllanthus urinaria preparations are reported to have a similar therapeutic effect as conventional IFN [ 26 , 28 ]. Although it seems that TCM can be used as alternative medicine for antiviral treatment, the antiviral effect needs to be evaluated in well-designed and randomized clinical trials.…”
Section: Drugs Available For Antiviral Therapy In Chinamentioning
confidence: 99%